Development of e-Module Using Problem-Based Learning Model Assisted by Heyzine Flipbook on Static Fluid Topic for Senior High School Students - Fadila, Muhamad; Khusaini, Khusaini; Hidayat, Arif (Jurnal Pendidikan Fisika dan Teknologi, 2025)
This study aims to develop a valid and practical problem-based learning e-module using Heyzine Flipbook to enhance student understanding of static fluid concepts. This study employed the Research and Development (R&D) methodology using the 4D Model. The participants included expert validators, consisting of media experts, material experts, practitioners, and fifty eleventh-grade students from various high schools. Data were collected through validation instruments and student response questionnaires, and the results were analyzed descriptively. The findings revealed that the developed e-Module fulfilled the criteria of being highly valid and practical. Media expert validation achieved an average score of 85%, while material expert validation obtained a score of 83.5%, indicating that the e-Module is suitable for use. Student responses to the e-Module were overwhelmingly positive, with a practicality score of 88%. This study suggests that PBL-based e-Modules can serve as an effective alternative learning medium to promote interactive learning and enhance the quality of physics education. Future research should focus on evaluating the effectiveness of this e-Module on a larger scale and further exploring its application in teaching static fluid concepts.